Change of Ownership and Financialization of the Agents: Analysis of the Curriculum of the Professionals in the Leadership Position in the Electricity Sector in Brazil (Global Journal of Human-Social Science, 2020)
The aim of this study is to approach the professional trajectory of Brazilians who occupied high positions in large companies. After the process of mergers and acquisitions, and privatization of companies, in the 90s in Brazil, we look for identify how, due to the new financial logic, elite professionals had to seek ways to reconstruct and rebuild their careers according to the new financial logic at the moment. The case of the Brazilian company, Eletropaulo, which went through restructuration, exemplifies this scenario, as it was a stateowned enterprise before and now privatized company. The central importance of studying the Brazilian electricity sector is that this sector has been subject to the most radical changes in financialization since 1990. In fact, these transformations are unprecedented in any other economy. This unique experience has led a number of other countries to examine the Brazilian model, sometimes in order to criticize it, but in other cases to emulate and develop it further. However, no study about the built of careers elite in this Brazilians context has so far been made.
Keywords: financialization; professional trajectory; quantitative analysis; culture; privatization